1986
DOI: 10.1259/0007-1285-59-699-251
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy of squamous carcinoma of the tonsil: an analysis of prognostic factors and of treatment failures

Abstract: A retrospective analysis of the results of treatment by primary irradiation of 87 cases of squamous-cell carcinoma of the tonsil at one institution over a 20-year period is presented. Survival at 5 years for all patients was 20%. The major determinants of survival were tumour size (T) and nodal status (N) at presentation. Degree of histological differentiation had no prognostic significance. Initial failure occurred in the primary tonsil site or in cervical lymph nodes in almost all cases. It is clear that tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A 20-year retrospective analysis of 87 cases of tonsillar SCC found that the major determinants of survival were tumor size and nodal status at presentation. 25 The degree of tumor differentiation had no prognostic significance. In contrast, a more recent study reported by Larsen et al 9 found tumor differentiation to be a strong prognostic factor for nodal metastasis, independent of other histological features.…”
Section: Discussionmentioning
confidence: 97%
“…A 20-year retrospective analysis of 87 cases of tonsillar SCC found that the major determinants of survival were tumor size and nodal status at presentation. 25 The degree of tumor differentiation had no prognostic significance. In contrast, a more recent study reported by Larsen et al 9 found tumor differentiation to be a strong prognostic factor for nodal metastasis, independent of other histological features.…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, the predictive value of the 7th edition of the TNM classification for oropharyngeal carcinomas, and for N classification in particular, has shifted over time as a consequence of the epidemic of HPV‐associated HNSCCs 13–34 . This shift prompted the publication of a new edition of the UICC staging system.…”
Section: Discussionmentioning
confidence: 99%
“…During multidisciplinary counseling, treatment plans were based on tumor size, neck staging, presence of distant metastases, tumor histology and cytology of metastases, feasibility of surgery, clinical condition, comorbidities, and histopathology of resection specimens in case of surgery. Elective treatment of the neck was performed routinely—also in the N0 neck—because of the high incidence of occult metastases in TSCC 15,19–21 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations